Hubungan Antara Sikap Higiene Tidur dan Faktor Lain dengan Angka Kejadian Insomnia pada Satuan Pengamanan (Satpam) dengan Kerja Gilir di PT. X - Intan Vindalia Dian Sari H; Ambar W. Roestam; Nurmiati Amir (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : Securities who undergo work-shift, are at risk for insomnia. Based on study by Didi Purwanto at Citeureup-Bogor cement factory at 2005, prevalence of insomnia on shift workers is 48.1% and is almost twice higher than non-shift workers.The aim of this research is to know the prevalence of insomnia and to determine factors that increase the risk of insomnia on security with shift work at PT. X. Method : Design of this study is cross-sectional which involved 107 securities with shift. Data collection used several questionnaires, including Sleep Hygiene Index questionnaire, Stress Diagnostic Survey questionnaire, Insomnia Rating Scale-KSPBJ questionnaire, and interview using MINI instrument. The prevalence of insomnia on securities with shift work at PT.X is 81.9%. Result : The result showed that poor sleep hygiene behavior increased the risk of insomnia almost 10 times higher than good sleep hygiene behavior (OR=9.820, 95%CI=1.185-81.413). Olderage, longer working hours, irregular pattern of work shift, and medium-high stresses did not increase the risk of insomnia on securities with shift work (p > 0.05). Discussion : Suggestion to security who undergoes shift should implement good sleep hygiene. For PT.X management, counseling about the health problems caused by shift work, especially insomnia every three months and taking health evalu ation at security who have insomnia everyone to three months are recommended.